Compensated orthogonal spread codes for full parallel usage of multi-transducer ultrasonic testing systems in NDE - Schäfer, Marius W.; Del Galdo, Giovanni; Fischer, Sarah C. L. (Frontiers in Acoustics, 2025)
IntroductionThe use of multi-transducer methods and equipment is common in non- destructive testing. These systems and methods provide increased accuracy or even enable test cases that cannot be carried out with single transducer testing. On the downside, these systems significantly increase execution time when the evaluation of a single channel or evaluation of crosstalk to other channels is performed sequentially. As the number of individual channels increases, so does the execution time and the amount of data. This paper presents the theoretical integration and experimental validation of orthogonal spread code sequences for multi-transducer ultrasonic testing.MethodsThe custom-built, two-channel ultrasonic test system and the measurement setup using a 60 mm-wide rectangular specimen are shown. The cross-correlation properties of random binary, random Gaussian and Gold codes, known from GPS, are compared for the code selection.ResultsThe Gold codes, the most promising set of codes, are experimentally investigated for suitability. Based on the results, upscaling potential of the method is presented based on a simulation using 9 code sequences summed with a random offset to a single array to replicate a 9-transducer setup. After compensating for the transfer function of the ultrasonic testing system, a localisation accuracy of less than 4 ns is achieved using a polynomial fit and a sampling interval of 8 ns.DiscussionBy incorporating this method into ultrasonic testing, measurement speed can be increased while stability and accuracy are improved.While codes with an amplitude close to the cross-correlation ratio will be difficult to detect, this method can be extended beyond 9 transducers for higher amplitudes, as long as the total amplitude does not exceed the maximum voltage limit of the electronic system.